(untitled) (The Pakistan Development Review, 2025)
Current account imbalance and concomitant macroeconomic instability in emerging market economies have been major issues of recent macroeconomic modelling. This paper addresses these issues by asking how international interdependence has impinged on key macroeconomic variables and policy options. There are three assets: domestic bonds, foreign bonds and money. Domestic bonds and foreign bonds are imperfect substitutes due to presence of risk premium. The striking features of the model include endogenous risk premium and balance sheet effect on investment demand due to exchange rate depreciation. We use a simple open economy structuralist macro model that explains the interaction between current account adjustment and exchange rate dynamics. The balance sheet effect and the risk premium together explain how fiscal expansion or monetary expansion may have both short run and long run contractionary effect on the output level with worsening current account balance in the short run. JEL Classifications: F41, F32, E52, E62 Keywords: Current Account, Exchange Rate, Risk Premium, Balance Sheet Effect